Grey theory study on the influence of karst-pile-soil coupling on the ultimate bearing capacity of pile foundation in karst development area. (January 2019) - He, Jingbin; Feng, Zhongju; Dong, Yunxiu; Chen, Huiyun; Huang, Zhouyi; Xia, Chengming; Zhao, Yawan; Hu, Haibo
Abstract: There are many factors influencing the ultimate bearing capacity of pile foundation in karst development area. The current design method usually adopts a large safety factor, which inevitably leads to an increase in engineering cost and a prolonged period. Grey theory is a kind of mathematical theory based on known information. It can describe the change law of unknown information by generating and developing some known information. Based on the above characteristics, combined with numerical simulation results, the effects of aspect ratio and karst scale on the ultimate bearing capacity of bridge piles are studied by using grey theory. The results show that the ultimate bearing capacity of piles increases with the increase of aspect ratio, and decreases with the increase of karst scale. The degree of influence of karst scale is larger than that of aspect ratio. Grey theory can better reflect the variation of ultimate bearing capacity of pile foundation under aspect ratio and karst scale, and the error between calculation result and numerical simulation result is about 9%. The grey theory can be applied to the estimation of the ultimate bearing capacity of bridge piles.